2014
DOI: 10.1016/j.neuron.2013.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Responses of C. elegans Chemosensory Neurons Are Preserved in Behavioral Dynamics

Abstract: Summary Animals track fluctuating stimuli over multiple timescales during natural olfactory behaviors. Here, we define mechanisms underlying these computations in Caenorhabditis elegans. By characterizing neuronal calcium responses to rapidly fluctuating odor sequences, we show that sensory neurons reliably track stimulus fluctuations relevant to behavior. AWC olfactory neurons respond to multiple odors with sub-second precision required for chemotaxis, whereas ASH nociceptive neurons integrate noxious cues ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
157
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(174 citation statements)
references
References 53 publications
16
157
1
Order By: Relevance
“…Similar biphasic filters have been found in numerous other systems (Hart and Alon, 2013;Kato et al, 2014;Nagel and Doupe, 2006); there they are proposed to support efficient coding (Atick and Redlich, 1990;Zhao and Zhaoping, 2011). Here, we add another aspect that makes biphasic filters advantageous: the two lobes correspond to two neuronal response features -tonic and phasic -and signal distinct song features -song amount and bout number.…”
Section: Linking Computations In the Auditory Pathway With Female Behmentioning
confidence: 52%
“…Similar biphasic filters have been found in numerous other systems (Hart and Alon, 2013;Kato et al, 2014;Nagel and Doupe, 2006); there they are proposed to support efficient coding (Atick and Redlich, 1990;Zhao and Zhaoping, 2011). Here, we add another aspect that makes biphasic filters advantageous: the two lobes correspond to two neuronal response features -tonic and phasic -and signal distinct song features -song amount and bout number.…”
Section: Linking Computations In the Auditory Pathway With Female Behmentioning
confidence: 52%
“…The prediction of turning frequency to the stimulus waveform compares favorably with experimentally observed behavior, suggesting that the linear filter captures much of the sensorimotor transformation underlying larval thermotaxis. We expect that the prediction could be further improved by including nonlinearities into the transformation (e.g., linear-nonlinear models) or additional factors (e.g., generalized linear models) (16,17).…”
Section: Resultsmentioning
confidence: 99%
“…(Schwartz et al 2006;Pillow et al 2008;Sharpee 2013;Aljadeff et al 2016)) but has also recently found applications in predicting behavior from both sensory stimuli and neuronal responses (e.g. (Kato et al 2014;Coen et al 2014;Schulze et al 2015;Clemens et al 2015a)). LN models treat the brain as a black box, i.e.…”
Section: The Approachmentioning
confidence: 99%
“…A simple generalization enables applying the STA approach to continuous outputs like neuronal calcium levels or the amplitude of the animal's communication signal (Kato et al 2014;Coen et al 2016). In these cases, the filter is estimated by weighting the stimulus by the response value.…”
Section: The Approachmentioning
confidence: 99%
See 1 more Smart Citation